Fault feature extraction and enhancement of rolling element bearing in varying speed condition. (August 2016) - Ming, A.B.; Zhang, W.; Qin, Z.Y.; Chu, F.L.
Abstract: In engineering applications, the variability of load usually varies the shaft speed, which further degrades the efficacy of the diagnostic method based on the hypothesis of constant speed analysis. Therefore, the investigation of the diagnostic method suitable for the varying speed condition is significant for the bearing fault diagnosis. In this instance, a novel fault feature extraction and enhancement procedure was proposed by the combination of the iterative envelope analysis and a low pass filtering operation in this paper. At first, based on the analytical model of the collected vibration signal, the envelope signal was theoretically calculated and the iterative envelope analysis was improved for the varying speed condition. Then, a feature enhancement procedure was performed by applying a low pass filter on the temporal envelope obtained by the iterative envelope analysis. Finally, the temporal envelope signal was transformed to the angular domain by the computed order tracking and the fault feature was extracted on the squared envelope spectrum. Simulations and experiments were used to validate the efficacy of the theoretical analysis and proposed procedure. It is shown that the computed order tracking method is recommended to be applied on the envelope of the signal in order to avoid the energy spreading and amplitude distortion. Compared with the feature enhancement method performed by the fast kurtogram and corresponding optimal band pass filtering, the proposed method can efficiently extract the fault character in the varying speed condition with less amplitude attenuation. Furthermore, do not involve the center frequency estimation, the proposed method is more concise for engineering applications. Abstract : Highlights: The iterative envelope analysis method is extended to the varying speed condition. A low pass filter is applied on the iterative envelope to enhance the fault feature. Simulations and experiments are used to validate the proposed method. The proposed method is more efficient than methods performed by band-pass filters.